A Randomized Trial Comparing Clinical Outcomes Between Zero-Profile and Traditional Multilevel Anterior Cervical Discectomy and Fusion Surgery for Cervical Myelopathy. Issue 5 (1st March 2018) - He, Shenghua; Feng, Hualong; Lan, Zhiming; Lai, Juyi; Sun, Zhitao; Wang, Yeguang; Wang, Jian; Ren, Zhiqiang; Huang, Feiqiang; Xu, Fuguang
Abstract : Study Design: Prospective randomized study from a single center Objective: The purpose of this study was to compare outcomes between a zero-profile (ZP) anterior cervical discectomy and fusion (ACDF) construct to a traditional ACDF with anterior cervical plate (ACP) in the treatment of multilevel cervical spondylotic myelopathy. Summary of Background Data: Multilevel cervical spondylotic myelopathy can be treated by a variety of techniques, most commonly with corpectomy, ACDF, posterior cervical fusion, or a combination of the three. Examples in the literature of comparative effectiveness of different anterior approach types are few. Methods: A total of 104 patients with multilevel cervical spondylotic myelopathy were randomized in equal proportion between treated with ACDF and ZP or ACDF with ACP. Clinical efficacy of two groups was evaluated preoperatively and at all postoperative time points through 2 years postoperative by the Japanese Orthopedic Association score and the neck disability index. Radiographic changes from baseline, including disc height and cervical lordosis, were evaluated at the same postoperative time points. Complications were assessed perioperatively and through 2 years postoperatively. Results: The ZP and ACP ACDF groups demonstrated substantially equivalent Japanese Orthopaedic Association, neck disability index, disc height, and lordosis improvements from baseline, which were maintained through 2 years postoperatively. Complications occurred in 4% of ZP and 17% of ACP patients ( P = 0.052), and zero (0%) ZP and four (8%) ACP patients reported hoarseness or dysphagia. Conclusion: ZP used in multilevel ACDF may obtain favorable clinical outcomes and a lower postoperative complication. Level of Evidence: 2